Convenient Synthesis of 3‐Deazapurine Nucleosides (3‐Deazainosine, 3‐Deazaadenosine and 3‐Deazaguanosine) Using Inosine as a Starting Material. Issue 11 (27th November 2021) - Hinotani, Naoto; Saito‐Tarashima, Noriko; Minakawa, Noriaki
Abstract: A convenient synthetic method for preparing 3‐deazapurine nucleosides (3‐deazainosine, 3‐deazaadenosine, and 3‐deazaguanosine) from inosine via a 5‐ethynyl‐1‐β‐D ‐ribofuranosylimidazole‐4‐carboxamide (EICAR) derivative, which is a key intermediate, is described. A large‐scale synthesis of an EICAR derivative starting from inosine was achieved in six steps via dinitrophenylation at the N 1 position followed by ring opening, iodination of the resulting 5‐amino group, and a palladium‐catalyzed cross‐coupling reaction. The resulting EICAR derivative was then converted into 3‐deazainosine, 3‐deazaadenosine, and 3‐deazaguanosine. This route enabled us to synthesize 3‐deazapurine nucleosides conveniently in good yields. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of 5‐ethynyl‐1‐β‐D ‐ribofuranosylimidazole‐4‐carboxamide (EICAR) derivative 6 Basic Protocol 2 : Preparation of 3‐deazapurine nucleosides 8, 11, and 14